(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
This paper argues that the notion of modernity has been confined to techno-industrial progress, rationality, individualism and to a narrow definition of the spirit of freedom but very meagre space has been given to the other notions and sensibilities in the discourse of modernity. It is because modernity has been hegemonized by the west wherein their values are projected as ‘modern’ or ‘rational’ and the values of the rest of the world are projected as ‘non-modern’ or ‘anti-modern’. This has created the perception of the world civilizations in terms of binary opposites of ‘self’ and ‘other’. The non-western man is the ‘other’, ‘superstitious’ and ‘irrational’ whereas a western individual belonging to a scientific civilization is, by the very application of this binary, as ‘rational’, ‘modern’ and ‘enlightened’. This division of the world into binaries because of the perceived modernity of the western civilization is at the heart of the Gandhi’s critique of modernity. It is this ‘arrogance of modernity’ or ‘hyper-modernity’ of the west that Gandhi has vehemently opposed. There are two different ways how scholars and analysts visualize Gandhi’s stance on modernity. On the one hand, some scholars construe Gandhi as an ultra-conservative while others go on to the other extreme of calling him a modernist who made modernity acceptable to the masses by putting it in the garb of tradition while others have labeled him as ‘postmodern’ because he challenged both the old and the new established orders. He challenged both the ‘ritual order of upper caste Hinduism’ and at the same time rejected the ‘high modernist order of the Nehruvian Congress’. Nevertheless, Gandhi gave new meaning to the very idea of tradition by juxtaposing it with modernity that was both original and path-breaking, thus, widened the notion and meaning of modernity beyond its narrower interpretation in the west.